2016
DOI: 10.1016/j.tem.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac GR and MR: From Development to Pathology

Abstract: The efficacy of mineralocorticoid receptor (MR) antagonism in the treatment of certain patients with heart failure has highlighted the pivotal role of aldosterone and MR in heart disease. The glucocorticoid (GC) receptor (GR) is also expressed in heart, but the role of cardiac GR had received much less attention until recently. GR and MR are highly homologous in both structure and function, although not in cellular readout. Recent evidence in animal models has uncovered a tonic role for GC action via GR in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 66 publications
(75 reference statements)
1
27
0
5
Order By: Relevance
“…Recent studies have shown that 11β-HSD1 is expressed in myocardial cells, including notably cardiac fibroblasts. Global 11β-HSD1 deficiency has effects on cardiac growth and physiological function that are more subtle than those associated with GR deletion (Oakley & Cidlowski 2015, Richardson et al 2016), or adrenalectomy (Cruz-Topete et al 2016), but nevertheless of physiological relevance. Importantly, genetic or pharmacological depletion of 11β-HSD1 also prevents adverse cardiac remodelling and the development of heart failure after MI (McSweeney et al 2010, Gordon et al 2014, White et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that 11β-HSD1 is expressed in myocardial cells, including notably cardiac fibroblasts. Global 11β-HSD1 deficiency has effects on cardiac growth and physiological function that are more subtle than those associated with GR deletion (Oakley & Cidlowski 2015, Richardson et al 2016), or adrenalectomy (Cruz-Topete et al 2016), but nevertheless of physiological relevance. Importantly, genetic or pharmacological depletion of 11β-HSD1 also prevents adverse cardiac remodelling and the development of heart failure after MI (McSweeney et al 2010, Gordon et al 2014, White et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…2A). Cardiomyocyte GR activation in the neonatal period promotes the switch from proliferative to hypertrophic growth (Richardson et al 2016). MR activation in the same period promotes proliferation (Feng et al 2013).…”
Section: β-Hsd1 In Postnatal Growth Of the Myocardiummentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of 11β-HSD2, endogenous glucocorticoids can bind to the mineralocorticoid receptor (MR) as well as the glucocorticoid receptor (GR) [37]. Both MR and GR belong to the same nuclear hormone receptor superfamily, and share high sequence identity.…”
Section: Introductionmentioning
confidence: 99%